A case study on inter-organisational technology transfer in the defence industry. (15th October 2021) - Bezuidenhout, Saija; Bean, Wilna L.
Abstract : Purpose: This paper aims to establish a systematically constructed defence offset technology transfer (TT) process description and to identify the process pain points and critical success factors from the supplier perspective. Design/methodology/approach: A novel integrated case study and Straussian grounded theory approach under the interpretative assumptions and purposive sampling in a global defence industry organisation are presented. Findings: The TT is approached from the process modelling point of view, and a detailed operations description covering the end-to-end TT process across a defence industrial participation project is presented. The findings suggest that local recipient's management, financial resources and planning, supply chain management and local production planning are the main factors of an efficient process. Research limitations/implications: This is a single case study, only reflecting the supplier view. Future research could explore the other dimensions of the process to confirm the identified factors playing a role over time. Originality/value: To date, the body of TT research has focused on the factors influencing the technology absorption and the identification of meta mechanisms between the supplier and recipient organisations in a context of a multinational corporation and as an intra-firm activity, providing little insight to the actual practical operational level TT process. This study seeks to fill this gap by advancing a more profound understanding of the process activities and the main factors through which the local recipient organisation can best influence the project's success and manage the inter-organisational TT operations more effectively in a highly technologically complex operational environment.